Report of the Working Group on Social Security for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission Government of India, 2001)
The Working Group on Social Security for the Tenth Five Year Plan (2002–2007) analyzed the status and gaps in social security provisions across India’s organized and unorganized workforce, which constitutes approximately 397 million workers, with only 28 million formally covered. The report highlights inadequacies in existing frameworks, such as the Employees’ State Insurance Act and Provident Fund schemes, which primarily benefit organized sector employees while leaving the vast unorganized sector largely unprotected. Key challenges include insufficient pension schemes, low awareness of worker rights, limited enforcement of labor laws, and wage disparities. Recommendations emphasize extending social security coverage to unorganized workers, including agricultural laborers, through targeted programs addressing medical care, accident benefits, and pensions. Legislative reforms such as enhancing the Minimum Wages Act, enforcing gratuity provisions, establishing a national minimum wage, and creating a unique worker identification system are proposed to improve compliance and equity. The report also stresses leveraging ICT for better service delivery, engaging NGOs and Panchayati Raj Institutions in awareness campaigns, and fostering community participation. By integrating organized and unorganized workers under a cohesive national policy, strengthening enforcement, and promoting public awareness, the Working Group advocates for a more inclusive, efficient, and equitable social security system that supports economic growth, protects vulnerable populations, and reinforces India’s welfare state commitments.
Government of India Planning Commission October-2001
Keywords: Social Security; Unorganized Sector; Organized Sector; Labor Laws; Minimum Wages; Pensions; Gratuity; Workers’ Rights; Public Awareness; National Policy; Enforcement; Economic Development